AREG+ regulatory T cells mediating myocardial repair and neovascularization after myocardial infarction - Yan Wang; Jiao Li; Yu Zhang; Pingping He; Weiwei Liu; Weirong Zeng; Chaofu Li; Yixuan Gao; Yongchao Zhao; Changyin Shen; Wenming Chen; Yunhang Li; et al. (Molecular Medicine)
Abstract Enhancing tissue repair and angiogenesis post-Acute myocardial infarction (AMI) is critical to improving cardiac function and preventing heart failure. Recent studies have highlighted the interaction between immune cells and endothelial cells in post-AMI angiogenesis, yet the specific contributions of different immune cell subsets remain poorly understood. Emerging evidence suggests the presence of a subset of regulatory T cells (Tregs) expressing Amphiregulin (AREG) in infarcted myocardial tissue, with AREG acting as a paracrine protein that plays a key role in angiogenesis. However, whether AREG⁺ Tregs mediate post-AMI angiogenesis and the underlying molecular mechanisms remain unclear. In this study, we demonstrate that Treg activation promotes tissue repair and improves cardiac function after AMI, although it does not significantly impact angiogenesis or endothelial cell behaviors. Notably, overexpression of AREG⁺ Tregs stimulates robust neovascularization post-AMI, reduces myocardial fibrosis, and further enhances cardiac function. Our in vitro data reveal that AREG⁺ Tregs secrete not only AREG but also angiogenic factors such as VEGF and FGF, which promote endothelial cell proliferation, migration, and tube formation. RNA sequencing analysis identifies FoxM1 as a key regulator of this angiogenic process in cardiac microvascular endothelial cells (CMECs). Importantly, inhibition of AREG in Tregs abolishes the FoxM1-dependent angiogenic response.In summary, we identified AREG⁺ Tregs as a distinct cell population driving neovascularization post-AMI, with FoxM1-mediated angiogenesis in CMECs. This may provide a foundation for harnessing specific Treg subsets for cardioprotection following AMI.